2019
DOI: 10.1002/jcp.29363
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐34a inhibits the proliferation, migration, and invasion of oral squamous cell carcinoma by directly targeting SATB2

Abstract: In various kinds of carcinomas, the special AT-rich sequence-binding protein 2 (SATB2) with its atypical expression promotes the metastasis and progression of the tumor, though in the oral squamous cell carcinoma (OSCC) its inherent mechanism and the status of SATB2 remain unclear. The role played by the SATB2 expression in the OSCC cell lines and tissue samples in the target of miR-34a downstream is the intended endeavor of this study. In te OSCCs the miR-34a expression was determined by quantitative real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Amplification or overexpression of ACTL6A leads to full occupancy of BAF complexes, giving rise to two mechanisms promoting SCC initiation and maintenance. ll promotes the survival and chemoresistance of SCCs partly by interacting with DNp63a (Chung et al, 2010;Ge et al, 2020b;Seong et al, 2015;Yu et al, 2017) (Figure 6D). Several other ACTL6A-dependent PRC target genes belong to the FOX family, members of which are often repressed by polycomb and poised for activation (Golson and Kaestner, 2016).…”
Section: Actl6a Overexpression Redistributes Polycomb Over the Genomementioning
confidence: 99%
“…Amplification or overexpression of ACTL6A leads to full occupancy of BAF complexes, giving rise to two mechanisms promoting SCC initiation and maintenance. ll promotes the survival and chemoresistance of SCCs partly by interacting with DNp63a (Chung et al, 2010;Ge et al, 2020b;Seong et al, 2015;Yu et al, 2017) (Figure 6D). Several other ACTL6A-dependent PRC target genes belong to the FOX family, members of which are often repressed by polycomb and poised for activation (Golson and Kaestner, 2016).…”
Section: Actl6a Overexpression Redistributes Polycomb Over the Genomementioning
confidence: 99%
“…SATB2 overexpression in HN4 cells promoted proliferation, migration, and invasion, as well as facilitating EMT and activating the Janus kinase (JAK)/STAT3 signaling pathway. These ndings suggest that SATB2 overexpression in important for progression in oncogenesis, like the role of SATB1 in breast cancer [23]. Because of the limited number of patients enrolled in this study, more patients from multiple institutions are needed to de nitively establish SATB2's overexpression pattern as well as its diagnostic utility in OSCC.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that IL-6 promotes head and neck tumor metastasis and EMT via the STAT3/SNAIL signaling pathway [24]. Like SATB1 in breast cancer [23], IL-6 promotes growth and invasion of breast cancer cells through STAT3dependent up-regulation of the NOTCH signaling pathway [20,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Besides WNT7B , other ACTL6A-dependent PRC targets known to play roles in SCC oncogenesis included TWIST1 , which is associated with epithelial–mesenchymal transition (EMT) in esophageal and head-and-neck SCCs (Jouppila-Matto et al, 2011; Lee et al, 2012); and SATB2 (special AT-rich binding protein 2), which promotes survival and chemoresistance of head-and-neck SCC cells in part by interacting with Δ Np63 α (Chung et al, 2010) and also drives carcinogenesis of oral SCC, colorectal cancer and osteosarcoma (Ge et al, 2020b; Seong et al, 2015; Yu et al, 2017) (Figure 5D). Several other ACTL6A- dependent PRC target genes belong to the forkhead box (FOX) family, members of which are often repressed by polycomb and poised for activation (Golson and Kaestner, 2016) (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%